The peculiarities of boxers with different motor phenotypes asymmetrical actions in changing kinematic situations - Malazoniya, I. G.; Gronskaya, A. S. (The Russian Journal of Physical Education and Sport, 2016)
The article deals with the consideration of functional asymmetry in boxing from the point of its influence on the orientation of active confrontation and the skills of the most effective use of tactics in spatio-temporal field of the ring. Material. The sign and degree of the upper and lower extremities dominance among qualified athletes (members of the national boxing team of Krasnodar territory) and the connection of the motor profile variants with the success of technical-tactical actions in the right and left-hand stand, in changing typical kinematic situations of the battle, are analyzed. Research methods: scientific and scientific-methodical literature analysis and summarizing, the leading arm and leg revelation using adapted to the specificity of a kind of sport range of tests, video analysis of the duration of strikes with the right and left hands when changing a mutual stand in the projection on a horizontal plane, the methods of mathematical statistics. Results. The motor preferences and the degree of asymmetry of boxers` upper and lower extremities are revealed. The received indices are combined into motor profiles taking into consideration the individual fighting stand. It is stated that the most preferable are the variants of cross asymmetry ("right hand - left leg", "left hand-right leg"). Biomechanical and statistical video analysis of the asymmetric technical actions with the left and the right hand, when changing a mutual stand in three relative positions, showed valid indices changes among 80% of boxers. Conclusion. The technique of a strike and defense in a fight mainly depends on a motor phenotype of a boxer, defining the asymmetry of his individual stand, speed and efficiency of the fulfilled actions at different distance from the opponent.